2014
DOI: 10.1098/rspb.2014.2259
|View full text |Cite
|
Sign up to set email alerts
|

Natural allelic variations of xenobiotic-metabolizing enzymes affect sexual dimorphism inOryzias latipes

Abstract: Sexual dimorphisms, which are phenotypic differences between males and females, are driven by sexual selection. Interestingly, sexually selected traits show geographical variations within species despite strong directional selective pressures. This paradox has eluded many evolutionary biologists for some time, and several models have been proposed (e.g. 'indicator model' and 'trade-off model'). However, disentangling which of these theories explains empirical patterns remains difficult, because genetic polymor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Interestingly, many genes involved in steroid metabolism, such as cytochrome P450 ( CYP ) genes, were found near the QTL [ 15 ], suggesting that variation in the size-specific expression of these steroid metabolism genes results in the interpopulation variation in sexual dimorphism in fin lengths. It has also been shown that polymorphisms in CYP genes are associated with variation in sexual dimorphism in the anal fin morphology between Japanese and Korean populations; high-activity alleles enhance sexual difference in anal fin shapes [ 21 ], supporting that CYP genes are responsible for the interpopulation variation in the ontogeny of sex steroid levels and resultant variation in fin lengths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, many genes involved in steroid metabolism, such as cytochrome P450 ( CYP ) genes, were found near the QTL [ 15 ], suggesting that variation in the size-specific expression of these steroid metabolism genes results in the interpopulation variation in sexual dimorphism in fin lengths. It has also been shown that polymorphisms in CYP genes are associated with variation in sexual dimorphism in the anal fin morphology between Japanese and Korean populations; high-activity alleles enhance sexual difference in anal fin shapes [ 21 ], supporting that CYP genes are responsible for the interpopulation variation in the ontogeny of sex steroid levels and resultant variation in fin lengths.…”
Section: Discussionmentioning
confidence: 99%
“…For example, androgens are known to increase the expression of male-specific appendages or ornaments but they also promote courtship behaviors and territorial aggressions [ 41 44 ]. In support of this, it has been demonstrated that male medaka from lower-latitude populations fight each other more frequently than do males from higher-latitude populations and that lower-latitude males also tend to court females more frequently [ 21 ]. Theoretically, such male-specific appendages and mating behaviors are thought to evolve through sexual selection [ 2 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The details are in the supplementary table S1. To explore the genetically-fixed gut length in medaka populations, we sampled 400 individuals from 40 wild-derived laboratory stocks that originated from wild populations, which had been maintained in a constant environment at an outdoor breeding facility, the University of Tokyo 11,23 Yongcheon, Maegok, Bugang, Sacheon, Shanghai. The subgroup names in parentheses are defined in our prior study 11 .…”
Section: Sampling and Measurement Of Gut Lengthmentioning
confidence: 99%
“…Impaired DSB repair was previously elucidated in the cells derived from a radiation-sensitive strain of medaka using immunofluorescence staining of γ-H2AX and phosphorylated DNA-PK at T2609 [15]. Recently, there are several studies using medaka to analyze the functional differences among genetic polymorphisms for understanding those in humans [1618]. Since medaka has highly differentiated geographical populations with large genetic diversity [19], the similar genetic polymorphisms equivalent to humans are occasionally found in the wild populations of medaka.…”
Section: Introductionmentioning
confidence: 99%